Swelling behavior of bisensitive interpenetrating polymer networks for microfluidic applications - Krause, A. T.; Zschoche, S.; Rohn, M.; Hempel, C.; Richter, Andreas; Appelhans, D.; Voit, Brigitte (Soft Matter, 2016)
Bisensitive interpenetrating polymer network (IPN) hydrogels of temperature sensitive net-poly(N-isopropylacrylamide) and pH sensitive net-poly(acrylic acid-co-acrylamide) for microfluidic applications were prepared via a sequential synthesis using free radical polymerization. The IPN indicated a suitable reversible alteration of swelling in response to the change in pH and temperature. The adequate change of the hydrogel volume is a basic requirement for microfluidic applications. Using the introduced correction factor f, it is possible to determine the cooperative diffusion coefficient (Dcoop) of cylindrical samples at any aspect ratio. The determined cooperative diffusion coefficient allowed the evaluation of varying swelling processes of different network structures. The presence of the second sub-network of the IPN improved the swelling behaviour of the first sub-network compared to the individual networks.
CRIS-Team Scopus Importer:2023-03-20